2016
DOI: 10.1111/apha.12646
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and vascular disease - a 30th anniversary update

Abstract: The endothelium can evoke relaxations of the underlying vascular smooth muscle, by releasing vasodilator substances. The best-characterized endothelium-derived relaxing factor (EDRF) is nitric oxide (NO) which activates soluble guanylyl cyclase in the vascular smooth muscle cells, with the production of cyclic guanosine monophosphate (cGMP) initiating relaxation. The endothelial cells also evoke hyperpolarization of the cell membrane of vascular smooth muscle (endothelium-dependent hyperpolarizations, EDH-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
661
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 741 publications
(686 citation statements)
references
References 1,041 publications
(1,045 reference statements)
10
661
1
14
Order By: Relevance
“…Endothelial dysfunction is generally characterized by a decrease in endothelial dependent relaxation. The vascular endothelium plays a vital role in the regulation of basal vascular tone through the synthesis and release of several vasodilators including nitric oxide (NO), prostaglandin I 2 (PGI 2 ) and endothelium-derived hyperpolarizing factor (EDHF) (7). It has been reported that endothelium-derived NO is a predominant mediator of endothelial-dependent relaxation in aortae, and its bioavailability is impaired in several pathophysiological states such as hyperlipidemia, metabolic syndrome, diabetes and hypertension (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction is generally characterized by a decrease in endothelial dependent relaxation. The vascular endothelium plays a vital role in the regulation of basal vascular tone through the synthesis and release of several vasodilators including nitric oxide (NO), prostaglandin I 2 (PGI 2 ) and endothelium-derived hyperpolarizing factor (EDHF) (7). It has been reported that endothelium-derived NO is a predominant mediator of endothelial-dependent relaxation in aortae, and its bioavailability is impaired in several pathophysiological states such as hyperlipidemia, metabolic syndrome, diabetes and hypertension (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…NO is generated from the conversion of L-arginine to L-citrulline by endothelial NO synthase (eNOS) and has a potent vasodilator, anti-inflammatory, and antithrombotic properties (6). Reduction of NO bioavailability, caused by reduced eNOS activity and/or accelerated NO degradation, results in impaired endothelium-dependent vasorelaxation, increased thrombus formation, and progressive atherogenesis (7). There is growing evidence that fructose fed animals exhibited impaired endothelium-dependent relaxation (8)(9)(10)(11) and decreased NO bioavailability (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although NO is by far the best‐characterized endothelium‐derived relaxing factor, others, such as prostacyclin and hydrogen peroxide, and endothelium‐derived constricting factors (eg, prostanoids and endothelin‐1) contribute to endothelial‐dependent vasomotion 61. Unfortunately, their impact on endothelial function, the development of CAD, and especially the role of exercise training on their regulation is less studied and needs further investigation.…”
Section: Mechanism 1: Partial Correction Of Endothelial Dysfunctionmentioning
confidence: 99%
“…Although the molecular basis responsible for vasculopathy in diabetes mellitus has been widely investigated, the innate pathogenic mechanisms affected various phases at the early stage of the disease have remained yet poorly understood (Bhatta et al, 2016). Diabetes-induced vasculopathy may be attributable to hyperglycemia, lipotoxicity, neurohumoral dysregulation of vascular function, increased prolonged exposure to oxidative stress, reduced production and release of nitric oxide, lowgrade microvascular inflammation, pro-thrombotic state, reduced ability to repair endothelial damage by recruitment of endothelial precursors, development of asymptomatic atherosclerosis (Bhatta et al, 2016;Lehoux and Jones, 2015;Leong et al, 2016;Vanhoutte et al, 2015). Indeed, hyperglycemia leads to accumulation of advanced glycation end-products (AGEs) that transduces inflammatory and proliferative response through reactive oxygen species generation, or through activation of Receptor for AGEs (RAGE)-mediated pathways (Yamagishi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%